The surge in borrowing needs of OECD governments Revised estimates for 2009 and 2010 Outlook - Blommestein, Hans J.. (OECD Publishing, 2010)
OECD governments are facing ongoing, unprecedented challenges in raising smoothly large volumes of funds at lowest possible cost, while balancing refinancing-, repricing- and interest rate risks. Amidst continued uncertainty about the pace of recovery as well as the timing and sequencing of the steps of the exit strategy, gross borrowing needs of OECD governments are expected to reach almost USD 16 trillion in 2009, up from an earlier estimate of around USD 12 trillion. The tentative outlook for 2010 shows a stabilising borrowing picture at around the level of USD 16 trillion. A looming additional challenge is the risk that when the recovery gains traction, yields will start to rise. Although there are signs that issuance conditions are becoming tougher, most OECD debt managers have been successful in financing the surge in funding needs. Less successful auctions can therefore best be interpreted as "single market events" and not as unambiguous evidence of systemic market absorption problems. The future could become more challenging though, given that rising issuance is occurring in tandem with increasing overall debt levels and debt service costs. In response, sovereign debt managers, with the essential support of the fiscal authorities, need to implement a timely and credible medium-term exit strategy to avoid future "crowding out" and systemic issuance problems, while reducing government borrowing costs